Pengaruh Berbagi Pengetahuan terhadap Perilaku Kerja Inovatif dengan Variabel Intervening Komitmen Afektif: Studi pada Perawat Rumah Sakit Roemani Muhamadiyah Semarang - Engel Tekege; Intan Ratnawati (Diponegoro Journal of Management, 2025)
Knowledge sharing is the practice of individuals within an organisation exchanging information, skills, data, and experiences to build mutual understanding and improve organisational performance. This study aims to analyse the effect of knowledge sharing on innovative work behaviour with affective commitment as a mediating variable. The study was conducted on permanent nurses at Roemani Muhammadiyah Hospital in Semarang using a quantitative approach. Data collection was carried out through a questionnaire distributed via Google Form to the entire population of 255 permanent nurses as respondents, using an accidental sampling technique, resulting in 100 samples, and analysed using the Structural Equation Modelling (SEM) method based on Partial Least Squares (PLS). The results of the study indicate that knowledge-sharing activities have a positive and significant effect on both affective commitment and innovative work behaviour. Furthermore, affective commitment was proven to partially mediate the relationship between knowledge sharing and innovative work behaviour. These findings contribute to management efforts to promote a culture of knowledge sharing and enhance innovation within the organisational environment.